Media Berbasis Budaya Lokal dalam Pembelajaran IPA SD - I Made Ari Winangun (Edukasi: Jurnal Pendidikan Dasar, 2020)
Media is an introduction to communication, one of which is in the learning process. Media as an introduction in the learning process is very necessary to bridge students in learning science. One type of media that is applied in elementary science learning is local culture-based media. The use of this media, is able to increase the understanding and achievement of student learning because learning science elementary schools that are based on local culture is very close to the daily lives of students. In this study a mapping of elementary school science learning grade IV is in accordance with the theme in the 2013 curriculum. Each theme that discusses the subject of natural science is presented through the local culture of Bali in accordance with the learning content. Local culture-based media in learning can be in the form of teaching materials or student worksheets. The presence of local culture-based media is able to increase students' motivation and learning activities which lead to increased learning outcomes. Keywords: Local Culture Based Media, Elementary Science Learning